Transient Neonatal Myasthenia Gravis: Case Report - Sara Sitar; Milena Treiber (Acta Medico-Biotechnica, 2023)
Purpose: Transient neonatal myasthenia gravis (NMG) results from the transplacental transfer of antibodies of mothers with an autoimmune form of myasthenia gravis. The clinical presentation develops in 10%–20% of their children. This study aimed to present a case of a newborn with transient myasthenia gravis (MG) born to a mother diagnosed with MG.Case presentation: The disease manifested itself as generalized hypotonia, weak cry, respiratory distress, poor sucking, and facial diplegia. The symptoms were usually self-limiting, and transient supportive treatment was required. A diagnostic test was a good clinical response of the child to the administration of an acetylcholinesterase inhibitor. After the clearance of antibodies from the child's blood, long-term therapy was not necessary and the disease resolved. Treatment was supportive and included the administration of smaller and more frequent meals via a tube, noninvasive or invasive support of respiratory function, and use of acetylcholinesterase inhibitors (neostigmine and pyridostigmine).Conclusion: Pediatric patients diagnosed with transient NMG are extremely rare in everyday clinical practice, and hence it is important to be familiar with it.